Chemistry of sea-salt particles and sea-salt fractionation in Antarctic region - Keiichiro Hara; Kazuo Osada; Masahiko Hayashi; Masanori Yabuki; Gen Hashida; Takashi Yamanouchi (Antarctic Record, 2010)
Observations of aerosol constituents and acidic gases were carried out at Syowa Station (1997-1998 and 2003-2006; JARE-38～ 39, and JARE-44～ 47) and Dome Fuji Station (1997, JARE-38). Seasonal variations and size distribution of sea-salt particles were compared between coastal and inland stations. Seasonal variations of the concentrations of sea-salt particles showed a minimum in the austral summer and higher during the winter at both stations due to strong winds and long-range transport. Sea-salt particles were mostly distributed in fine (D_p: 0.2-2.0 μm) and ultra-fine (D_p<0.2 μm) modes at Syowa Station. Particulate Cl^- and Br^- are liberated preferentially from sea-salt particles through the heterogeneous reactions at Syowa and Dome Fuji Stations in the summer. The molar ratio of Cl^- Na^+ and Br^- Na^+ at Syowa Station decreased to ca. 0.5 and ～0, respectively, in summer. Fewer sea-salt particles were modified at Syowa Station during the winter, whereas sea-salt particles were modified through the year at Dome Fuji Station. In particular, sea-salt particles were modified with NO_3^- and its precursors at Dome Fuji Station during the winter. The concentrations of gaseous inorganic chlorine species (mostly HCl) and bromine species at Syowa Station were 0.2-9.4 nmol m^<-3> and below the detection limit (BDL)-1.5 nmol m^<-3>, respectively. Sea-salt fractionation (SO_4^<2-> depletion) due to Mirabilite formation was identified not only at Syowa Station but also at Dome Fuji Station. Seasonal variation of molar ratio of Mg^<2+> Na^+ showed higher ratios at lower temperature. The range and temperature dependence of Mg^<2+> Na^+ strongly suggested that other sea-salt fractionation (e.g., formation of gypsum and hydrohalite) occurred in the Antarctic coasts in addition to Mirabilite formation. Because of different seasonal variation and range of Mg^<2+> Na^+ between Dome Fuji and Syowa Stations, sea-salt fractionation may proceed even in the inland area.